Effects of key parameters on performance of a pre-cooled core engine based on the closed helium cycle - Tong-Ling, Ma; Xue-Feng, Jiang; Guo-Dong, Liu; Zhen-De, Liu; Han, Gao; Xue-Gang, He; Peng-Cheng, Du (Frontiers in Mechanical Engineering, 2023)
A pre-cooled combined engine based on a closed helium (He) cycle offers high specific thrust and high specific impulse. Therefore, evaluating the performance of such an engine is crucial for engine applications and key technology research. This study employs an analytical approach to investigate the effects of key parameters on the performance of a pre-cooled core engine, assuming a perfect gas model. The findings revealed that the specific thrust and specific impulse of the pre-cooled core engine are related to the pressurized-coefficient of the airflow passage and equivalence ratio. An increase in the pressurized-coefficient leads to an increase in both specific thrust and specific impulse. However, within a certain range, although the specific thrust is positively correlated with the equivalence ratio, the specific impulse is greatly reduced. With specific component parameters and a fixed thermodynamic cycle, a minimum equivalence ratio exists that satisfies the cyclematching requirement. Moreover, the value of the minimum equivalence ratio is related to the closedcycle efficiency. For a pre-cooled core engine with a simple closed-He cycle, the minimum equivalence ratio is approximately 2.5-3.5. Nomenclature Variables F thrust sF specific thrust I S specific impulse HC helium compressor HT helium turbine f fuel air air